Estimation of ventilation rate in a piglet house considering ventilation system characteristics. (March 2023) - Choi, Young-bae; Kim, Jun-gyu; Cho, Jeong-hwa; Lee, Sang-yeon; Park, Se-jun; Decano-Valentin, Cristina; Jeong, Deuk-young; Lee, In-bok
Abstract : In mechanically ventilated piglet houses, ventilation is considered the most important aspect that can enhance the rearing environment. However, the airflow rate of fans can be less than the design rate due to pressure losses caused by operating conditions. To ensure the accurate estimation of the airflow rate, pressure loss factors should be evaluated since they have a strong influence on ventilation. In this study, pressure losses were evaluated through field experiments with various inlet types (side window, ceiling slot), outlet types (side and chimney exhaust fan), and operating conditions (fan speed, inlet opening size). A fan airflow rate formula accounting for the characteristics of ventilation systems was developed based on the fan performance reported by the manufacturer (designed performance) and orifice theory. Compared with in-situ and design fan performance, the in-situ airflow rate reduced by an average of 7–35% due to pressure losses. The pressure loss of the chimney exhaust fan was higher than that of the side exhaust fan due to the long duct and the position of the fan. The ventilation rate for the ceiling slot inlet was prone to overestimation due to a higher resistance curve coefficient (0.4) than that of the side window inlet. The developed ventilation rate formula was validated using 360 cases and it showed high accuracy (side exhaust fan R 2 > 0.9947, chimney exhaust fan R 2 > 0.9947 ). Thus, the evaluated pressure loss factors and the developed ventilation rate formula can be applied for the design of ventilation systems in piglet houses. Highlights: Evaluation of pressure loss factors according to ventilation system in piglet house. In-situ fan perforamcnce estimated by design fan performance data. Developing a ventilation rate equation using opening size, fan speed.